Appearance-Related Communication Mediates the Link Between Self-Objectification and Health and Well-Being Outcomes. (1st October 2014) - Arroyo, Analisa; Segrin, Chris; Harwood, Jake
Abstract: Grounded in objectification theory, the 2 studies presented here predicted that self-objectification is positively related to appearance-related communication (i.e., fat talk and old talk), and, in turn, appearance-related communication is associated with health and well-being outcomes. Results from Study 1, which investigated only fat talk, revealed that fat talk significantly mediated the relationship between self-objectification and body dissatisfaction, drive for thinness, bulimia, and self-esteem. Study 2 sought to replicate the findings from Study 1, as well as extend appearance-related communication to old talk. Fat talk was found to mediate the relationships between self-objectification and body dissatisfaction, drive for thinness, bulimia, depression, and diet. Old talk significantly mediated the relationships between body dissatisfaction, drive for thinness, and bulimia.